Image quality in low-dose multidetector computed tomography: a pilot study to assess feasibility and dose optimization in whole-body bone imaging. - Gleeson TG; Byrne B; Kenny P; Last J; Fitzpatrick P; O'Gorman P; Eustace SJ (Canadian Association of Radiologists Journal, 2010)
Objective: To study the impact of dose parameters on image quality at whole-body low-dose multidetector computed tomography (CT) in an attempt to derive parameters that allow diagnostic quality images of the skeletal system without incurring significant radiation dose in patients referred for investigation of plasma cell dyscrasias. Methods: By using a single cadaver, 14 different whole-body low-dose CT protocols were individually assessed by 2 radiologists, blinded to acquisition parameters (kVp and mAs, reconstruction algorithm, dose reduction software). Combinations of kVps that range from 80-140 kVp, and tube current time product from 14-125 mAs were individually scored by using a Likért scale from 1-5 in 4 separate anatomical areas (skull base, thoracic spine, pelvis, and distal femora). Correlation between readers scores and effective doses were obtained by using correlation coefficient statistical analysis, statistical significance was considered P < .01. Interobserver agreement was assessed by using a Bland and Altman plot. Interobserver agreement in each of the 4 anatomical areas was assessed by using kappa statistics. A single set of parameters was then selected for use in future clinical trials in a cohort of patients referred for investigation of monoclonal gammopathy, including multiple myeloma. Results: Several sets of exposure parameters allowed low-dose whole-body CT to be performed with effective doses similar to skeletal survey while preserving diagnostic image quality. Individual reader's and average combined scores showed a strong inverse correlation with effective dose (reader 1, r = -0.78, P = .0001; reader 2, r = -0.75, P = .0003); average combined scores r = -0.81, P < .0001). Bland and Altman plot of overall scores shows reasonable interobserver agreement, with a mean difference of 1.055. Conclusion: Whole-body low-dose CT can be used to obtain adequate CT image quality to assess normal osseous detail while delivering effective doses similar to those associated with conventional radiographic skeletal survey.